2016
DOI: 10.1136/archdischild-2016-310917
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the weight of ethnically diverse children attending an Australian emergency department: a prospective, blinded, comparison of age-based and length-based tools including Mercy, PAWPER and Broselow

Abstract: ObjectiveTo prospectively compare the actual weights of Australian children in an ethnically diverse metropolitan setting with the predicted weights using the Paediatric Advanced Weight Prediction in the Emergency Room (PAWPER) tape, Broselow tape, Mercy system and calculated weights using the updated Advanced Paediatric Life Support (APLS), Luscombe and Owens and Best Guess formulae.MethodsA prospective, cross-sectional, observational, blinded, convenience study conducted at the Children's Hospital at Westmea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 28 publications
5
37
1
2
Order By: Relevance
“…The original PAWPER tape achieved an exceptionally high overall level of accuracy in this study sample, similar to that previously reported from non-obese populations [6,23,24]. The accuracy in obese children was poor, however, similar to previous findings from studies in populations with a high prevalence of obesity [4,5].…”
Section: Discussion the Performance Of The Weight Estimation Systems supporting
confidence: 77%
See 2 more Smart Citations
“…The original PAWPER tape achieved an exceptionally high overall level of accuracy in this study sample, similar to that previously reported from non-obese populations [6,23,24]. The accuracy in obese children was poor, however, similar to previous findings from studies in populations with a high prevalence of obesity [4,5].…”
Section: Discussion the Performance Of The Weight Estimation Systems supporting
confidence: 77%
“…These findings echo previous studies in which these three methods have been compared [5,6,23]. Given the consistently higher accuracy of the dual length-and habitus-based weight estimation systems (such as the Mercy method and the PAWPER tapes) when compared with length-only systems (such as the Broselow tape) it is hard to justify the continued use of the Broselow tape.…”
Section: A Comparison Between the Pawper XL Tape And The Other Methodscontrasting
confidence: 35%
See 1 more Smart Citation
“…[10,11] However, recent studies on the original PAWPER tape in very obese populations, and with novice users, failed to show the degree of accuracy reached in studies in less obese populations. [8,10,[12][13][14] An important contributor to the reduced accuracy of the PAWPER tape was inaccurate assessment of body habitus in these obese children. [12,15] The development of a less subjective and more standardised method of assessing habitus could therefore potentially improve the functioning of the PAWPER system in different populations and with users of different experience.…”
Section: Researchmentioning
confidence: 99%
“…Some studies have shown that the Pediatric Advanced Weight Prediction in the Emergency Room (PAWPER) tape is more accurate in predicting the correct weight as compared to Broselow tape345; others have suggested that the PAWPER tape has not been able to replicate its initial impressive performance6 and that none of the currently available methods is optimum5. Adjusting the estimated weight based on body habitus seems to be theoretically advantageous, but Georgoulas and Wells4 have stated that such adjustments have had only a minimal impact on the overall performance of the PAWPER tape.…”
mentioning
confidence: 99%